TEMPERATURE DEPENDENCE OF THE POLARIZED ELECTRONIC ABSORPTION SPECTRA OF OLIVINES. PART I - FAYALITE - Ullrich K.; Becker K.D.; Langer K. (My University, 2002)
Polarized electronic absorption spectra of orthorhombic fayalite, Fe2SiO4, [E || a(|| Z),E || b(|| X), E || c(|| Y)], space group Pbnm, have been studied in the temperature range 293 ≤T/K ≤ 1273. The spectra were analysed into component bands originating from spin-allowed dd transitions of iron(II) at the different sites, M1 and M2, in the structure. The assignments of bands, made on the basis of the polarization dependence of the spectra and considerations of transition energies, were confirmed by the analysis of the temperature-dependent spectra. The temperature dependencies of integral intensities, half band widths and energy positions of absorptions bands caused by Fe2+ on the different octahedral sites, M1 and M2, were evaluated for the individual transitions. Independent of the site symmetry, absorption bands shift to lower energies and half band widths increase on rising temperature. The temperature dependence of band intensities depends on site symmetry. The integral intensities are found to increase with temperature for the transition metal ion on a centrosymmetric site, or remain constant when the site is missing an inversion centre. This is consistent with the general conclusion of Taran et al. (1994).